Against race- and class-based pedagogy in early childhood education - Smith, Stephanie C. (Stephanie Carol) (New York, NY : Palgrave Macmillan, 2015)
'Against Race- and Class-Based Pedagogy in Early Childhood Education examines differing classroom pedagogies in two early childhood programs serving vulnerable populations in Chicago, one program Reggio Emilia-inspired, while the other uses a more didactic pedagogy. The structure of clas'--
Machine generated contents note: -- PART I: LEGACIES OF RACE AND CLASS BASED PEDAGOGIES IN EARLY CHILDHOOD -- 1. A Look inside Two Chicago Preschools -- 2. Early Childhood Policy and Practice -- 3. Urban Early Childhood -- PART II: INSIDE OF CLASSROOMS, INSIDE OF PEDAGOGY -- 4. Classroom Teaching -- 5. The Development Of The Whole Child -- 6. Classroom Management -- 7. Roles of Teachers and Language Codes -- 8. Field Trips and Demonstrating Internalization -- 9. Engaging Parents -- PART III: DIFFERING PEDAGOGIES, DIFFERING OUTCOMES -- 10. Pedagogical Differences and Child Outcomes -- 11. Against Race- and Class- Based Teach in Early Childhood Education.
Includes bibliographical references and index.
Keywords: Children with social disabilities -- Education (Early childhood) -- Illinois -- Chicago -- Case studies; Early childhood education -- Social aspects -- Illinois -- Chicago -- Case studies; Reggio Emilia approach (Early childhood education) -- Illinois -- Chicago -- Case studies